(untitled) (International Journal of Engineering and Computer Science, 2017)
In recent days different access control methods have been proposed to secure the ATM Transaction from unauthorized access. This paper describes a method of implementing two way authentication. The first one is normal PIN verification method and if the password is correct then it goes to the second step of authentication (i.e.,) two way authentication method. In that if the authorized person replied YES through their mobile, then corresponding transaction takes place. Otherwise it switches ON the buzzer, automatically close the door of ATM centre and LCD will show the detail about ATM theft to the higher authorities.